Correlation of lymphocyte-to-monocyte, platelet-to-lymphocyte, and neutrophil-to-lymphocyte ratios with skin-symptom improvement following antimicrobial treatment in palmoplantar pustulosis - Kuninori Iwayama; Takayuki Manabe; Ko-Ichi Ohtaki; Masayuki Chuma; Mari Kishibe; Masaru Honma; Yoshikazu Tasaki (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Palmoplantar Pustulosis (PPP) is a chronic inflammatory skin disease that presents as pustules on the palms and soles. There are no oral medications for patients with mild PPP, with apremilast, a new oral PDE4 inhibitor, indicated for moderate to severe cases of the disease. We previously reported that antimicrobial therapy improved PPP symptoms according to dermatological assessment (improvement or not), with a negative correlation between lymphocyte-to-monocyte ratio (LMR) and improvement of symptoms. However, the correlation between PPP area-and-severity index (PPPASI) and LMR could not be evaluated. Methods Herein, we used the PPPASI to evaluate the effect of antimicrobial therapy and investigate whether LMR, platelet-to-lymphocyte ratio (PLR), and neutrophil-to-lymphocyte ratio (NLR), which reflect inflammation, could be used as indicators of treatment efficacy. Eleven patients who were administered an antimicrobial agent were enrolled. Treatment efficacy was measured by PPPASI 25 and PPPASI symptom subscales. Treated patients were compared with six control patients who had no change in PPP therapy during the observation period. In addition, the improvement in LMR, PLR, and NLR with antimicrobial treatment was analyzed and correlated with PPPASI. Results The antimicrobial drug treatment group was more likely to achieve PPPASI 25 than the control group. PPPASI symptoms subscale for erythema and desquamation were improved compared to those in the control group. There was a correlation between changes in PPPASI correlated with LMR, PLR, and NLR from antimicrobial treatment. Conclusions Our results suggest antimicrobial drug treatment as therapy for mild PPP. In addition, LMR, PLR, and NLR are potential biomarkers of antimicrobial drug treatment. Trial registration This study is not considered a clinical trial because it is observational.